ANALISIS PENGARUH LIKUIDITAS ATAS PERTAMBAHAN PROFIT DI PERUSAHAAN PERTAMBANGAN YANG LISTING DI BEI - Iman Indrafana Kusumo Hasbullah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2021)
This research is to identify and explain the analysis of the effect of liquidity (current rasio, quick rasio, cash rasio) of the profit growth in the mining company listed on the Stock Exchange in the period 2012 - 2014. The type of study used by researchers is associative. The number of the population that is 41 companies. The sampling method used is sampling purposive sampling basis.